SOCIODEMOGRAPHIC AND ILLNESS SEVERITY CORRELATES OF COPING STYLES AMONG CAREGIVERS OF SCHIZOPHRENIA OUTPATIENTS IN NIGERIA - Ighedosa, Osemhen Bartholomew; Kilani, Hassan Taiwo; Olorunsogbon, Olorunyomi Felix; Onasile, Olusina Funmi; Aigbedion, Osalumese Chris (African Journal of Social and Behavioural Sciences, 2026)
Caring for patients with schizophrenia may be associated with considerable stress, and caregivers adopt various coping styles to mitigate untoward consequences arising from the caregiving role in a bid to maintain mental homeostasis. This study aims to assess coping style patterns and correlates among caregivers of schizophrenia outpatients at the Neuropsychiatric Hospital Aro, Abeokuta, Ogun State, South-west, Nigeria. It was a crosssectional analytical study involving 244 caregivers. Data collection was carried out over a four-month period. Coping Orientations to Problems Experienced (COPE), Brief Psychiatric Rating Scale (BPRS) and sociodemographic questionnaire were used for data collection, while Mini International Neuropsychiatric Interview (MINI-Plus) re-validated the diagnosis of schizophrenia. Bivariate analysis was used to test for associations between variables and multivariate analysis assessed independent predictors. The most endorsed coping style was problem-focused coping, while the least was avoidance, with mean scores of 12.65 and 6.22, respectively. Being separated, divorced or widowed (β = 0.56; p = 0.04), not being supported in caregiving role (β = 0.42; p = 0.01) and duration of care > 60 months (β = 0.47; p = 0.01) independently predicted emotion-focused coping. Being male (β = 0.58; p = 0.01), nonimmediate family member of patient (β = 1.71; p = 0.003), not being supported in caregiving role (β = 0.72; p = 0.02) and having a tertiary level education (β = 1.70; p = 0.001) were independent predictors of problem-focused coping. Being female (β = 0.73; p = 0.01), supported in caregiving role (β = 0.97; p = 0.004), having primary level education (β = 1.01; p = 0.02) and duration of care ≤ 60 months (β = 1.03; p = 0.004) independently predicted socially supported coping. While avoidance coping was not independently predicted by any of the variables, it was significantly associated with being < 40 years of age (p = 0.001) and being single (marital status) (p = 0.022). Patients’ illness severity was not associated with caregivers’ coping style in a statistically significant manner. This study revealed that caregivers' coping styles in schizophrenia outpatients are significantly influenced by sociodemographic factors rather than patients’ illness severity, and the preponderant use of problem-focused coping may indicate a desire to actively cope with stress. It underscores the central role of caregiver sociodemographic characteristics in shaping adaptive coping, highlighting the need for targeted, contextually relevant interventions that address caregiver vulnerabilities and strengths in enhancing coping style, which is crucial to improving patients' quality of care.